First description of natural Ehrlichia canis and Anaplasma platys infections in dogs from Argentina - Eiras, Diego Fernando (2013)
Bacteria belonging to the Anaplasmataceae family are vector transmitted agents that affect a variety of vertebrate hosts including the tick-borne pathogens Ehrlichia canis and Anaplasma platys, which cause canine monocytic ehrlichiosis and cyclic thrombocytopenia, respectively. These two infections, typically reported from tropical and sub-tropical regions, have not been previously reported in dogs from Argentina. A total of 86 blood samples from dogs with suspected rickettsial disease and 28 non-suspected dogs were studied. Analysis included evaluation of hematological findings, PCR for Ehrlichia and Anaplasma species and sequencing of the positive PCR products. E. canis was detected in the blood of six dogs and A. platys in eighteen. All the dogs categorized as non-suspected were negative by PCR. Co-infection with Hepatozoon canis and Babesia vogeli was documented. This first report of E. canis and A. platys infections in dogs from Argentina indicates that these tick-borne infections have a considerably broader range than previously recognized in South America.